The Role of Government in Supervision of Protected Forests in Konawe District - Sahili, La Ode; Asy'ary, Ayuningtiyas Putri Mumpuni Halim; Fahrul, Muhammad (Santoso Academy Network, 2023)
This study aims to determine the role of forestry officials in monitoring the Protected forests in Konawe District and the factors that influence the role of forestry officials in monitoring the Protected forests in Konawe District. The informants in this study were employees at the UPTD KPH Unit Xiii Laiwoi Barat, Konawe Regency, 7 of whom were employees, heads of UPTD KPH Unit Xiii Laiwoi Barat Konawe Regency, community leaders, forest monitoring field officers, heads of forest protection and security and communities who have committed violations in protected forest areas. This research is descriptive qualitative. The type of data used is primary and secondary data. Data collection techniques by observing, studying documentation, and interviews. The results of this study are, 1) The role of the UPTD FLaiwoi Barat Konawe Regency in monitoring protected forests includes the roles of facilitators, regulators, dynamic actors, and coordinators that have been going well, 2) Factors influencing the Government in Controlling Protected Forests in Konawe Regency is the human resource factor as well as the regulatory factor